Respuesta :

Answer:

Step-by-step explanation:

1) -4(2w - 5z): We are going to expand this term by distributing -4 to both 2w, and -5z. To do this, multiply -4 by each of these terms. (-4 * 2w) = -8w and (-4 * -5z) = 20z. So, your final answer is -8w + 20z, or 20z -8w(both are equal).

2) Take out the GCF to factor the equation. In this case, the GCF would be 3b. Divide 3b by each of the existing terms. 6ab/ 3b = 2a; -12bc/3b = -4c; -3bd/3b = -d. Put those terms together and you get 3b(2a - 4c - d). Hope this helps! If not, feel free to ask additional questions.